(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Myelolipoma is a rare benign hormonally inactive adrenal neoplasm containing mature adipose tissue and a variable amount of haematopoietic elements.Their mostly small size,unilateral site and clinical quiescence are accountable for predominantly incidental disclosure. A symptomatic case of myelolipoma was presented in our hospital with generalized body swelling ,body rash and intermittent dull abdominal pain .He had H/O taking steroid for last 10 yrs to increase body weight and for better felling . All laboratory investigations were found within normal limit and he was referred to our department for radiological investigations. Plain X-ray, USG and CT scan of abdomen was done which revealed an well capsulated circumscribed highly echogenic , fat density soft tissue mass in right lumbar region which was suspected as suprarenal mass possibly myelolipoma and it was confirmed by FNAC as myelolipoma of right adrenal gland. J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 34-36